Evaluasi Program Muhadharah di MTs Pondok Pesantren Hidayatullah Medan - Qomariah. S, Nurlala; N, Nurmawati; A, As’ad (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study was conducted to determine the muhadharah program at MTs Pondok Pesantren Hidayatullah Medan, how the evaluation of the muhadharah program at MTs Pondok Pesantren Hidayatullah, what obstacles or barriers are faced in implementing the muhadharah program at MTs Pondok Pesantren Hidayatullah Medan and how to overcome them. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The subjects of this study were the Principal, Muhadharah Supervisor Teacher, Muhadharah Caregiver and Supervisor, Student Council (OSIS), and Students who have done Muhadharah. The results of the study indicate that the muhadharah program carried out at MTS Pondok Pesantren Hidayatullah Medan is carried out based on the division of tasks that have been determined. There are those who act as openers or presenters (moderators), prayer readers, and the student council or (OSIS) as technicians for the implementation of muhadharah. The evaluation of the muhadharah program at MTS Pondok Pesantren Hidayatullah Medan was conducted after the completion of the muhadharah activity. The obstacles or barriers faced in the implementation of the muhadharah program at MTs Pondok Pesantren Hidayatullah Medan and how to overcome them: 1) lack of time. 2) facilities and infrastructure that are less supportive. 3) different language skills of students.